Converting Thioether Waste into Organic Semiconductors by Carbon–Sulfur Bond Activation. (6th March 2019) - Zhu, Ting; Jiang, Longfeng; Li, Ying; Xie, Zengqi; Li, Zijie; Lv, Lei; Chen, Hao; Zhao, Zhiyuan; Jiang, Lang; Tang, Benzhong; Huang, Hui
Abstract: A goal for human society is to convert organic waste into valuable materials. Herein, 2‐(methylthio)‐bezothiazole (MTBT), an important organic waste in urban runoff, was catalytically converted into a series of organic semiconductors through carbon–sulfur bond activation. The efficient conversion of various substrates with different aromatic moieties and reacting functional groups (tin and boron) proved the generality of this novel diarylation Liebeskind–Srogl methodology. Moreover, the resulting organic semiconductors showed excellent performance in field effect transistors and cell imaging. This contribution presents an excellent example of converting organic waste into valuable materials and may open a new avenue to utilizing widely available aromatic thioethers.